Manfaat Edukasi Menggosok Gigi Terhadap Kemampuan Menggosok Gigi Pada Kondisi Down Syndrome dengan Media Visual - Aini, Widyati Nur; Santoso, Tri Budi; Harumi, Linda (Jurnal Empathy Pengabdian Kepada Masyarakat, 2023)
Background: Oral hygiene problems in children with Down Syndrome (DS) are challenging due to delayed motor and cognitive development that affects their independence in brushing their teeth. The purpose of this community service project was to determine the benefits of tooth brushing education using visual media on the tooth brushing skills of 8 children with DS in the partner region. Methods: The method used was direct education and training with visual media delivered to children and caregivers during several sessions. Evaluation was conducted through observation and measurement of toothbrushing skills before and after the intervention. Results: The results showed a significant improvement in toothbrushing skills, with 80% of participants experiencing an improvement in their ability to perform this activity independently. The addition of visual media proved effective in improving the fine motor skills required for tooth brushing. Conclusion: The provision of visual media was effective in improving tooth brushing skills in children with DS. This activity can be continued to provide tangible benefits in improving the quality of life of children with DS while supporting their families and caregivers.